1998
DOI: 10.1161/01.atv.18.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Spontaneous Aortic Disease in Young and Old Rabbits

Abstract: Abstract-The pattern of spontaneous lipid deposition around aortic branch ostia was mapped in New Zealand White rabbits aged 1 month or 2 to 6 years. The young rabbits were studied within 1 day of weaning, and the older rabbits had been maintained on a low-protein, low-fat diet. Plasma concentrations of total cholesterol for the two groups averaged 75 and 18 mg/dL, respectively. Aortas were fixed in situ at a pressure of 90 to 100 cm H 2 O, stained with oil red O, and photographed en face under an epifluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 27 publications
4
55
2
Order By: Relevance
“…Spontaneous disease in young and old rabbits fed the unsupplemented base diet from this supplier has been described in a previous report 5 and was not reassessed. The diet was administered over a period of 15 weeks, except that 1 rabbit from each group was killed after 13 weeks to monitor the progression of disease; these 2 animals did not differ in any significant way from the remainder of their respective groups, and data obtained from them are included in the analyses described below unless otherwise stated.…”
Section: Protocol Used In Trial Imentioning
confidence: 91%
See 2 more Smart Citations
“…Spontaneous disease in young and old rabbits fed the unsupplemented base diet from this supplier has been described in a previous report 5 and was not reassessed. The diet was administered over a period of 15 weeks, except that 1 rabbit from each group was killed after 13 weeks to monitor the progression of disease; these 2 animals did not differ in any significant way from the remainder of their respective groups, and data obtained from them are included in the analyses described below unless otherwise stated.…”
Section: Protocol Used In Trial Imentioning
confidence: 91%
“…The animals were fed a diet (RABMA, Special Diet Services), described in detail elsewhere, 5 to which the manufacturer had added cholesterol (derived from sheep wool, Peboc) in soya oil. Spontaneous disease in young and old rabbits fed the unsupplemented base diet from this supplier has been described in a previous report 5 and was not reassessed.…”
Section: Protocol Used In Trial Imentioning
confidence: 99%
See 1 more Smart Citation
“…1996). Previous work (Barnes and Weinberg 1998) has shown that the precision of such visual estimates is acceptable. As in our earlier studies, the line spacing of the grid was equivalent to 120 µm before magnification.…”
Section: Lesion Mapping By Established Techniquementioning
confidence: 94%
“…Lipid deposits near rabbit aortic branches were mapped using the new scanner-based technique and, for comparison, with the photomicrographic technique used in previous studies (Barnes and Weinberg 1998Forster et al 1996;McGillicuddy et al 2001;Richards and Weinberg 2000). The rabbits were randomly selected from a large group fed a cholesterol-and L-arginine-enhanced diet as part of a trial examining the influence of L-arginine on experimental atherosclerosis (Weinberg and Cremers 2003).…”
Section: Methodsmentioning
confidence: 99%